(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
The title of the research: The effectiveness of time management for principals of basic education schools in performing their tasks (a field study by monitoring the education of Al-Zahraa) The aim of the research: to identify the effectiveness of time management for personal tasks related to the principals of basic education schools in monitoring the education of Al-Zahra and to identify the effectiveness of time management for the supervisory technical tasks related to the principals of basic education schools to monitor the education Research Methodology: To conduct the research according to its objective objectives, the researchers used the descriptive method in this research. Research community: The research community consists of principals of basic education schools in the supervision of Al-Zahra’s education, which are (12) principals, including (09) males and (03) female principals. Research Tool: To answer the research questions, the research used the questionnaire as a tool for collecting data and information, which was built by the two researchers and directed to principals of basic education schools to monitor the education of Al-Zahra. Research results: the majority of the sample members dedicate part of their time to discuss some educational issues with teachers, and the majority of the sample members allocate part of their time to exchange their educational ideas with the school family, and the majority of the sample members follow the organization of school exams according to the schedule.